EVALUATION OF THE THERMAL COMFORT IN CONTACT WITH CERAMIC TILES - Effting, C.; Güths, S.; Alarcon, O. E. (Revista de Engenharia Térmica, 2006)
In places where people are bare feet, the thermal sensation of cold or hot depends on the environmental conditions and material properties including its microstructure and crustiness surface. The uncomforting can be characterized by heated floor surfaces in external environments which are exposed to sun radiation (swimming polls areas) or by cold floor surfaces in internal environments (bed rooms, path rooms). The property named thermal effusivity which defines the interface temperature when two semiinfinite solids are putted in perfect contact. The introduction of the crustiness surface on the ceramic tiles interferes in the contact temperature and also it can be a strategy to obtain ceramic tiles more comfortable. Materials with low conductivities and densities can be obtained by porous inclusion are due particularly to the processing conditions usually employed. However, the presence of pores generally involves low mechanical strength. This work has the objective to evaluate the thermal comfort of ceramics floor obtained by incorporation of refractory raw materials (residue of the polishing of the porcelanato) in industrial atomized ceramic powder, through the thermal and mechanical properties. The theoretical and experimental results show that the porosity and crustiness surface increases; there is sensitive improvement in the comfort by contact.